Exploring the influence of carbon sources and salinity on the growth of microalgae - Choong Xin Yi; Teh Hui Ying; Lam Man Kee; Raviadaran Revathi; Chai Yee Ho; Tan Inn Shi; Foo Henry Chee Yew; Wong Voon-Loong; Loy Adrian Chun Minh (E3S Web of Conferences)
In the domain of microalgae cultivation, the selection of carbon source and salinity profoundly impacts the growth and metabolic activity of species like Chlorella sp. Carbon sources and salt serve as vital substrates, dictating not only biomass production but also shaping cellular processes essential for various applications, particularly as agricultural biofertilizers. This study investigated the impact of different carbon sources and varying concentrations of sodium chloride (NaCl) on the growth of Chlorella sp. It was found that CO2 bubbling significantly improved microalgae growth, resulting in a notable 5.60% increase compared to cultivation with sodium bicarbonate. Within a span of 14 days, Chlorella sp. reached its peak biomass of 1.32 g/L ± 1.2% under CO2 bubbling, outperforming NaHCO3 cultivation, indicating a more efficient carbon utilization. Furthermore, the study revealed that Chlorella sp. achieved its highest biomass and lipid yield under CO2 bubbling cultivation without the addition of NaCl (1.32 g/L ± 1.2% and 0.43 g/L ± 3.0 % respectively), while a NaCl concentration of 0.5 M yielded the highest lipid content (34% ± 1.8 %) but had relatively low lipid yield at 0.21 g/L ± 5.0%. This underscored the impact of NaCl stress on the growth and lipid content of Chlorella sp.